Coulomb explosion imaging of CH3I and CH2ClI photodissociation dynamics - Allum, F; Burt, M; Amini, K; Boll, R; Köckert, H; Olshin, P; Bari, S; Bomme, C; Brauße, F; Cunha De Miranda, B; Düsterer, S; Erk, B; et al. (AIP Publishing, 2018)
The photodissociation dynamics of CH3I and CH2ClI at 272 nm were investigated by time-resolved Coulomb explosion imaging, with an intense non-resonant 815 nm probe pulse. Fragment ion momenta over a wide m/z range were recorded simultaneously by coupling a velocity map imaging spectrometer with a pixel imaging mass spectrometry camera. For both molecules, delay-dependent pump-probe features were assigned to ultraviolet-induced carbon-iodine bond cleavage followed by Coulomb explosion. Multi-mass imaging also allowed the sequential cleavage of both carbon-halogen bonds in CH2ClI to be investigated. Furthermore, delay-dependent relative fragment momenta of a pair of ions were directly determined using recoil-frame covariance analysis. These results are complementary to conventional velocity map imaging experiments and demonstrate the application of time-resolved Coulomb explosion imaging to photoinduced real-time molecular motion.